Information Flow, Volatility and Spreads of Infreuently Traded Nasdaq Stocks - WU, Chunchi (Institutional Knowledge at Singapore Management University, 2004)
This paper examines the information flow, return volatility, and trading costs of infrequently traded stocks. A mixture-of-distribution model is employed to decompose volume into informed and liquidity components. It is found that the intensity of informed trading is higher for infrequently traded stocks. This higher intensity of informed trading causes larger spreads. The positive volatility–volume relationship is much stronger when informed volume replaces raw volume in the volatility regression. A striking negative relationship between volatility and liquidity volume is uncovered. Finally, prices of infrequently traded stocks are more sensitive to informed trading than those of frequently traded stocks. [Copyright 2004 Elsevier]